Status Kesehatan Mental Ibu Hamil pada Kegiatan Antenatal Care (ANC) di UPTD Puskesmas Manggar Balikpapan, September–Oktober 2023: Hasil Penelitian - Noviane Angrella; Isabela Ariane (Cermin Dunia Kedokteran, 2025)
Introduction: Maternal mental health is an important yet often overlooked issue, both globally and nationally. About 10% of pregnant women experience mental health problems during pregnancy, with prevalence rates tending to be higher in developing countries. Methods: This descriptive study involved 100 pregnant women who attended routine antenatal care at UPTD Puskesmas Manggar between September and October 2023. The study aimed todetermine the prevalence and characteristics of maternal mental health status. Data were collected through interviews and the Self Report Questionnaire-20 (SRQ-20). Results: A total of 24% pregnant women were found to have common mental disorders, with fatigue being the most frequently reported symptom. The majority of those affected was multiparous (58.3%), in the third trimester of pregnancy (58.3%) and had no history of abortion (91.7%). Conclusion: The relatively high prevalence of common mental disorders during pregnancy underscores the importance of implementing routine mental health screening as an integral part of antenatal care at the primary healthcare level.